Determination of 137Cs activity in soil from Qatar using high-resolution gamma-ray spectrometry. (October 2016) - Al-Sulaiti, Huda; Nasir, Tabassum; Al Mugren, K.S.; Alkhomashi, N.; Al-Dahan, N.; Al-Dosari, M.; Bradley, D.A.; Bukhari, S.; Matthews, M.; Regan, P.H.; Santawamaitre, T.; Malain, D.; et al.
Abstract: With interest in establishing baseline concentrations of 137 Cs in soil from the Qatarian peninsula, we focus on determination of the activity concentrations in 129 soil samples collected across the State of Qatar prior to the 2011 Fukushima Dai-ichi nuclear power plant accident. As such, the data provides the basis of a reference map for the detection of releases of this fission product. The activity concentrations were measured via high-resolution gamma-ray spectrometry using a hyper-pure germanium detector enclosed in a copper-lined passive lead shield that was situated in a low-background environment. The activity concentrations ranged from 0.21 to 15.41 Bq/kg, with a median value of 1 Bq/kg, the greatest activity concentration being observed in a sample obtained from northern Qatar. Although it cannot be confirmed, it is expected that this contamination is mainly due to releases from the Chernobyl accident of 26 April 1986, there being a lack of data from Qatar before the accident. The values are typically within but are sometimes lower than the range indicated by data from other countries in the region. The lower values than those of others is suggested to be due to variation in soil characteristics as well as metrological factors at the time of deposition. Highlights: A baseline for the radionuclide 137 Cs in soil samples collected from Qatar was established. 129 soil samples collected across the landscape. Samples were collected before the most recent accident "the 2011 Fukushima Dai-ichi NNP accident". The highest activity concentration was found to be 15.41±0.67Stat. and 0.11Syst. The relatively high concentrations can be attributed to rain washout.